Implementation and evaluation of a quality improvement initiative to reduce late gestation stillbirths in Australia: Safer Baby Bundle study protocol - C. J. Andrews; D. Ellwood; P. F. Middleton; A. Gordon; M. Nicholl; C. S. E. Homer; J. Morris; G. Gardener; M. Coory; M. Davies-Tuck; F. M. Boyle; E. Callander; et al. (BMC, 2020)
Abstract Background In 2015, the stillbirth rate after 28 weeks (late gestation) in Australia was 35% higher than countries with the lowest rates globally. Reductions in late gestation stillbirth rates have steadily improved in Australia. However, to amplify and sustain reductions, more needs to be done to reduce practice variation and address sub-optimal care. Implementing bundles for maternity care improvement in the UK have been associated with a 20% reduction in stillbirth rates. A similar approach is underway in Australia; the Safer Baby Bundle (SBB) with five elements: 1) supporting women to stop smoking in pregnancy, 2) improving detection and management of fetal growth restriction, 3) raising awareness and improving care for women with decreased fetal movements, 4) improving awareness of maternal safe going-to-sleep position in late pregnancy, 5) improving decision making about the timing of birth for women with risk factors for stillbirth. Methods This is a mixed-methods study of maternity services across three Australian states; Queensland, Victoria and New South Wales. The study includes evaluation of 'targeted' implementer sites (combined total approximately 113,000 births annually, 50% of births in these states) and monitoring of key outcomes state-wide across all maternity services. Progressive implementation over 2.5 years, managed by state Departments of Health, commenced from mid-2019. This study will determine the impact of implementing the SBB on maternity services and perinatal outcomes, specifically for reducing late gestation stillbirth. Comprehensive process, impact, and outcome evaluations will be conducted using routinely collected perinatal data, pre- and post- implementation surveys, clinical audits, focus group discussions and interviews. Evaluations explore the views and experiences of clinicians embedding the SBB into routine practice as well as women's experience with care and the acceptability of the initiative. Discussion This protocol describes the evaluation of the SBB initiative and will provide evidence for the value of a systematic, but pragmatic, approach to strategies to reduce the evidence-practice gaps across maternity services. We hypothesise successful implementation and uptake across three Australian states (amplified nationally) will be effective in reducing late gestation stillbirths to that of the best performing countries globally, equating to at least 150 lives saved annually. Trial registration The Safer Baby Bundle Study was retrospectively registered on the ACTRN12619001777189 database, date assigned 16/12/2019